PROSEDUR PENERAPAN PAJAK PENGHASILAN PASAL 21 ATAS KARYAWAN TETAP MENGGUNAKAN METODE E-SPT PADA PT. X DI KANTOR KONSULTAN PAJAK PT OAKNEY CONSULA INDONESIA - Linda Antika, (2021)
Income Tax 21 is a type of tax imposed on income which can be in the form of salaries, wages, honoraria, allowances or other payments received by employees, non-employees, ex-employees, severance pay recipients made by individual domestic Tax Subjects. One source of state revenue is from the tax sector, because taxes are the largest source of state revenue in the State Budget (APBN). In the current state of the Covid-19 virus pandemic, at least there are several policies launched by the government to anticipate the achievement of the intended tax revenue target. One of them is the application of online taxation so that taxpayers do not need to go to the tax office in carrying out taxation. But at this time there are still many taxpayers who are confused and do not even understand how to calculate the amount of income tax from the income they receive and report it online. From these problems, the procedures made in this study can help readers, especially taxpayers who are still confused about calculations, making e-SPT, payments, and online tax reporting. By using these applications that have been provided by the Directorate General of Taxes, the process of calculating and reporting Income Tax Article 21 for Permanent Employees can be done quickly, easily, and automatically and will minimize errors such as manual calculations that allow for errors, and can reduce errors in data management so that the resulting information is faster and more accurate.